Ambient vibration testing and seismic behavior of historical arch bridges under near and far fault ground motions - Sevim, Baris; Atamturktur, Sez; Altunisik, Ahmet Can; Bayraktar, Alemdar (SPRINGER, 2016)
This study investigates the effects of near and far fault ground motion on the seismic behavior of historical arch bridges through a combined numerical and experimental evaluation. The approach undertaken begins with finite element modeling of the arch bridge and identification of the most significant vibration modes of the bridge through ambient vibration testing. Uncertain parameters of the finite element model are then revised through systematic comparisons of the measured vibration models to those that are predicted by the model. The revised finite element model is used to predict the time history response for displacements and stresses through which the effect of the finite element model updating on model predictions are evaluated. Furthermore, displacements and stresses obtained considering both near and far fault ground motions are then compared. Results indicate that near fault ground motion imposes higher seismic demand on the arch bridge observed in both higher displacements and stresses.
Keywords: Ambient vibration testing; Finite element model revision; Historical arch bridge; Near and far fault ground motion; Seismic behavior; NEAR-FAULT; IDENTIFICATION; Engineering; Geology